PECULIARITIES OF THE Z14XEP ENGINE VIBRATION AT IDLE SPEED UNDER POWER STEERING LOAD - Kubich, Vadim; Cherneta, Oleg; Kanskii, Anton (Problems of Friction and Wear, 2024)
The paper presents the results of determining the amplitude-frequency characteristic of the Z14XEP engine vibration of the Opel Astra G (F69) at idle speed depending on the steering wheel position. The opposite of changes in the values of the amplitude and frequency of mechanical vibrations of the engine on its supports was determined: an increase in amplitude and a decrease in frequency under the condition of the beginning of the movement of the hydraulic fluid through the power cylinder of the hydraulic booster. The actuation of the hydraulic boost system with an electric pump drive generally causes an increase in the amplitude of engine oscillations by 24.2% in the longitudinal and vertical planes, which occurred before the fluid was replaced, and by 14.4% after its replacement. It was determined that, regardless of the state of the hydraulic fluid at the beginning of its circulation through the cavities of the amplifier’s power cylinder, the frequency of mechanical vibrations of the engine decreases in the longitudinal and vertical planes by 25%. In the transverse plane, the oscillation frequency is reduced by 35%, except when the hydraulic fluid is changed, when the oscillation frequency remains unchanged. It has been established that the quality of the hydraulic fluid of the power steering system significantly affects the change in mechanical vibrations of the engine only when the steering wheel is deviated from the neutral position. It was determined that a decrease in the viscosity of the new hydraulic fluid by 8.3% compared to the fluid that was replaced causes changes only in the amplitude of engine oscillations. In the longitudinal plane, the oscillation amplitude decreases by 13.3%, in the vertical plane - by 15.1%, and in the transverse plane, the oscillation increases by 25.4%. Reducing the viscosity of the hydraulic fluid used reduced the resistance to its movement through the holes, channels and pipelines of the power steering system and reduced the power take-off to drive the power steering pump.